Salivary ki-67 and micronucleus assay as potential biomarker of OSCC in betel nut chewers - Maulina Triani; Haris B Widodo; Dody Novrial; Dewi Agustina; Gita Nawangtantrini (Wolters Kluwer Medknow Publications, 2021)
Introduction: Oral cancer is often associated with various factors, such as betel nut consumption, which usually causes specific premalignant lesions. The most common oral cancer is oral squamous cell carcinoma (OSCC) which has a low 5-year survivor rate because early detection of the malignancies is not widely used and not routinely carried out in dental practice. Early detection of malignancy can be done by measuring the salivary Ki-67 level and micronucleus assay from the buccal smear. Aims and Objectives: The study aimed to examine the potency of the salivary Ki-67 level and micronucleus assay for early detection of OSCC in betel nut chewers. Materials and Methods: This study was conducted in 17 betel nut chewers and 17 healthy people as a control group. Saliva was collected with the passive drooling technique and then analyzed using Enzyme-linked immunosorbent assay (ELISA). Buccal smears were taken, then a cytological slide was made and stained using Papanicolaou. Settings and Design: This study was a cross-sectional analytic survey that was conducted in the Banyumas District of Indonesia with a post-test- only control group design. Statistical Analysis: The statistical analysis used is a non-parametric test using Mann-Whitney and Kruskal-Wallis tests. Results: There was a significant difference between the Ki-67 level and micronucleus in the betel nut chewers group and the control group. There was a significant difference between Ki-67 and micronucleus levels in the various types of oral lesions that were found in the betel nut chewer's group. Conclusion: Examination of Ki-67 and micronucleus assay is effective as an alternative early biomarker for OSCC.